The Influence of Whistleblowing System Implementation and Human Resource Competence on Fraud Prevention in the Inspectorate Office of Polewali Mandar Regency - Riana Anggraeny Ridwan; Nursyam Anwar (Economics and Digital Business Review, 2026)
This study aims to analyze the influence of whistleblowing system implementation and human resource competence on fraud prevention efforts at the Inspectorate Office of Polewali Mandar Regency. In this context, Human Resource (HR) competence is viewed as a primary pillar in establishing accountable and transparent financial governance. Using a quantitative research design, primary data were collected through questionnaires from the entire population of 37 auditors at the research site; therefore, a total sampling (saturation sampling) technique was employed. The data were analyzed using multiple linear regression to test the significance of the variables' effects both individually (partially) and collectively (simultaneously). This study examines how individual capacity—encompassing knowledge, skills, and professional behavior—can strengthen internal oversight systems to minimize fraudulent practices. The findings confirm that, partially, the implementation of the whistleblowing system provides a positive and significant contribution to mitigating fraud risks. Similarly, human resource competence is proven to have a positive and significant effect on fraud prevention efforts. When tested simultaneously, both variables have a significant impact on preventing fraud. These results imply the necessity of optimizing reporting systems and strengthening HR capacity through continuous competency development as a core organizational